1994
DOI: 10.1143/jjap.33.4320
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Absolute Densities of Si, SiH and SiH3in Electron Cyclotron Resonance SiH4/H2Plasma

Abstract: We study a new mechanism to dynamically break supersymmetry in the E 8 × E 8 heterotic string. As discussed recently in the literature, a long-lived, meta-stable nonsupersymmetric vacuum can be achieved in an N = 1 SQCD whose spectrum contains a sufficient number of light fundamental flavors. In this paper, we present, within the context of the hidden sector of the weakly and strongly coupled heterotic string, a slopestable, holomorphic vector bundle on a Calabi-Yau threefold for which all matter fields are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…[6][7][8] Our current knowledge of the deposition mechanisms is inferred largely from macroscopic observations, such as the radical concentrations in the plasma during deposition 8,9 and the variation of the deposition rate with plasma conditions 10,11 obtained using various plasma and surface diagnostics. 10,[12][13][14][15][16][17][18][19] However, the reaction mechanisms between the species from the gas phase and the deposition surface are largely unascertained; even the identities of species that get incorporated into the film during growth are still under debate. 8,9,16,[20][21][22][23][24] Atomic-scale simulation can be used as a valuable tool to enhance our fundamental understanding of the plasma-surface reaction processes that occur during deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Our current knowledge of the deposition mechanisms is inferred largely from macroscopic observations, such as the radical concentrations in the plasma during deposition 8,9 and the variation of the deposition rate with plasma conditions 10,11 obtained using various plasma and surface diagnostics. 10,[12][13][14][15][16][17][18][19] However, the reaction mechanisms between the species from the gas phase and the deposition surface are largely unascertained; even the identities of species that get incorporated into the film during growth are still under debate. 8,9,16,[20][21][22][23][24] Atomic-scale simulation can be used as a valuable tool to enhance our fundamental understanding of the plasma-surface reaction processes that occur during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In fact, the precursor itself may be a function of deposition conditions. For example, it has been shown that Si is the predominant radical in electron cyclotron resonance plasma deposition of a-Si:H. 18 A sticking coefficient of 0.05-0.3 for the SiH 3 radical on a-Si:H surfaces has been reported in the literature; 28,[30][31][32][33] the sticking coefficient expresses the total reaction probability of the radical on the deposition surface including adsorption and abstraction. Several radical-surface reaction processes a͒ Author to whom correspondence should be addressed; electronic mail: dimitris@calypso.ucsb.edu have been proposed including mechanisms for abstraction of H atoms from surface sites by impinging SiH 3 radicals, diffusion of SiH 3 radicals on the surface until they find reactive sites on the surface where they can attach to, and reaction of two SiH 3 radicals adsorbed on the surface to form Si 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The UVAS measurement, using a silicon hollow cathode lamp as the light source, was used to measure the absolute densities of the atomic silicon in the gas phase. 19,20 The transition 3 p 2 2 P 2 Ϫ3 p4s 3 P 2 line of atomic silicon atom at 251.6 nm was used for the measurement. On the other hand, no simple measurement method has been established for obtaining the absolute density of atomic hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Yamamoto et al reported that the contribution of the Si atoms to thin-film formation was approximately 3.3 times as large as that of SiH 3 radicals in a ECR SiH 4 /H 2 plasma. 5) Murata et al reported that the growth of microcrystalline silicon with a preferential crystalline orientation is dependent on the balance between silicon and hydrogen atom densities in pulse-modulated ultrahigh-frequency SiH 4 /H 2 plasma. 6) Moreover, the Si atom reacts with the SiH 4 molecule at a high reaction rate and produces higher order silane-related radicals.…”
Section: Introductionmentioning
confidence: 99%